Access to Antihypertensive Medicines at the Household Level: A Study From 8 Counties of Kenya - Syed, Naureen; Rockers, Peter C; Vian, Taryn; Onyango, Monica; Laing, Richard O; Wirtz, Veronika J (Global heart, 2018)
Estimates of hypertension prevalence in Kenya range from 12.3% to 50.1% nationally. Of those diagnosed, only 1 in 5 were taking medication. This study aims to describe the access to antihypertensive medicines at the household level in 8 counties of Kenya, including factors associated with the location of purchase. A household survey was conducted asking individuals with a diagnosis and prescription of antihypertensive medicines about the location of diagnosis and purchase of medicines, the availability of medicines at home, and the costs of medicines per month. A logistic regression model explores the relationship between patient characteristics and the probability that patients bought medicines at a public facility. Of 445 individuals diagnosed and prescribed medicines for hypertension, 20.9% were also diagnosed with another noncommunicable disease, including diabetes or asthma. The majority of study subjects received their diagnosis at a public hospital (67.5%) but the most common place of medicine purchase was a retail pharmacy (33.6%). Some study subjects bought their medicines at a public hospital (21.1%). The most frequent answer for not having medicines at home was that they could not afford their medicines (50.0%). Purchase in the public sector was associated with being less wealthy, having >1 noncommunicable disease, and living in urban areas. Affordability remains an important barrier to hypertension treatment access in Kenya. Programs to promote access to affordable treatment need to take into account that diagnosis of disease and choice of medicines takes place largely in the public sector, whereas the private sector is the gatekeeper for purchase of medicines.